Fostering Authenticity and Disciplinary Dialogue in the Age of AI - Schmöckel, Sabrina; Sloane, Hannah Sabrina

How to Conduct Participatory Creative Visual Methods With Young Adults - Lin-Januszewski, Liang-Wen

„Ein Komponistenleben des 20. Jahrhunderts“. Erste Bestandsaufnahme und Forschungsfragen zu Hans Werner Henzes Privatbibliothek als Sondersammlung - Tumat, Antje (Musik, Netzwerke, Selbstzeugnisse. Aktuelle Forschung zu Hans Werner Henze)
Henzes Privatbibliothek aus seinem Besitz in La Leprara bei Marino südlich von Rom, in dem er fast fünfzig Jahre seines Lebens verbracht und viele seiner großen Werke geschrieben hat, wurde nach dem Verkauf des Anwesens der Bibliothek des Musikwissenschaftlichen Seminars der Universität Paderborn/Hochschule für Musik Detmold per Schenkung als Sondersammlung übergeben. Die Privatbibliothek ist nunmehr vollständig inventarisiert und somit der Öffentlichkeit zugänglich gemacht. Der Text beschreibt in einer ersten Bestandsaufnahme den Charakter und die Schwerpunkte dieser Sammlung und stellt erste Forschungsfragen an den Bestand: Er fragt etwa nach den Erkenntnissen, die sich aus den über 600 handschriftlichen Widmungen in Büchern und über 150 Widmungen in Noten im Hinblick auf Henzes persönliches Netzwerk und seine Biografie ergeben und wertet einige Widmungskonvolute aus. Abstract (EN) Henze's personal library, which belonged to him in La Leprara near Marino south of Rome, where he spent almost fifty years of his life and wrote many of his important works, was donated to the library of the Musicology Seminar of the University of Paderborn/Detmold University of Music as a collection after the sale of the estate. The private library has now been completely catalogued and is thus accessible to the public. The text provides an initial overview of the character and focus of this collection and poses research questions about the holdings: For example, it asks what insights can be gained from the more than 600 handwritten dedications in books and over 150 dedications in sheet music with regard to Henze's personal network and his biography, and evaluates some of the collections of dedications.
Keywords: Hans Werner Henze; Privatbibliothek; Neue Musik

Musik, Netzwerke, Selbstzeugnisse. Aktuelle Forschung zu Hans Werner Henze
Der Sammelband veröffentlicht die Beiträge des internationalen Symposiums zu Hans Werner Henze, das im Dezember 2022 in Detmold stattfand und aktuelle Beiträge zur Henze-Forschung mit unterschiedlichsten inhaltlichen Schwerpunkten wie Filmmusik, Gender Studies oder Musikanalyse versammelt. Nach zwei Aufsätzen zu neuen Henze-Briefausgaben (Irmlind Capelle / Elena Minetti / Dennis Ried / Antje Tumat einerseits und Andreas Hérm Baumgartner / Wolfgang Rathert andererseits) und einem ersten Überblick über Henzes Privatbibliothek als Sondersammlung (Antje Tumat) diskutiert Adrian Kuhl Die Zusammenarbeit Tatjana Gsovskys und Hans Werner Henzes beim Ballett Der Idiot. Zafer Özgen beschäftigt sich anschließend mit Kompositionsstrategien in Henzes frühen Opern, Federica Marsico betrachtet die Figur des Orpheus bei Henze aus Gender-Perspektive und Benedikt Leßmann widmet sich Henzes Filmmusik. Den Abschluss bildet ein Roundtable mit Zeitzeugen, bei dem ehemalige Kolleginnen und Kollegen, Freunde und andere mit Henze verbundene Personen aus ihrer Zusammenarbeit mit Henze berichten. Teilnehmende waren Henzes langjähriger Freund und enger Mitarbeiter in Montepulciano Gastón Fournier-Facio (Rom) und der Regisseur, Geschäftsführer der Henze-Stiftung und letzte Lebensbegleiter Henzes Michael Kerstan (Nürnberg), Simon Obert von der Paul Sacher Stiftung (Basel), dem Aufbewahrungsort der Sammlung Hans Werner Henze, sowie Peter Petersen (Hamburg) als Stellvertreter der frühen musikwissenschaftlichen Henze-Forschung.

Zu Heidegger - Kommunikationsanalytische Studien - Markewitz, Friedrich
Martin Heideggers Einfluss reicht bis heute weit über enge disziplinäre Grenzen hinaus in die verschiedenen Geistes- und Kulturwissenschaften sowie die gesamtgesellschaftliche Öffentlichkeit hinein. Gleichzeitig werden er und seine Philosophie, insbesondere seit der Veröffentlichung seiner Denktagebücher, der ‚Schwarzen Hefte‘, aufgrund nationalsozialistischer Verstrickungen und antisemitischer Konnotationen kontrovers diskutiert. Trotz seiner diskursiven Herausgehobenheit und Relevanz stehen linguistische Aufarbeitungen zu Heideggers Kommunikationsverhalten bis heute weitestgehend aus. Die vorliegende kommunikationsanalytische Studie versteht sich als erster umfassender Versuch, Heideggers Kommunikationsverhalten in den Blick zu nehmen, um Charakteristika wie Problematiken des Heideggerischen Sprachgebrauchs aufzuarbeiten sowie zu reflektieren.
Keywords: Linguistische Hermeneutik; Kommunikationsanalyse; Invektivitätsforschung; Begriffsarbeit

Sprache im erkenntnistheoretischen Werk Ludwik Flecks – Reflexionen und Anschlüsse - Markewitz, Friedrich; Ptashnyk, Stefaniya (Aptum - Zeitschrift für Sprachkritik und Sprachkultur)
This article examines the role of language in Ludwik Fleck’s epistemological work. Two objectives are pursued: Firstly, Fleck’s statements on language scattered throughout his oeuvre are to be systematized and reflected upon. Secondly, the question is asked of which statements of linguists and philosophers from the 19th and 20th centuries can be related to Fleck's work. The basic idea is that Fleck's reflections on thought styles and thought collectives can also be applied to his work to identify possible influences and correlations between Fleck’s remarks on language and those of other philosophers and linguists. Analyzing Fleck's ideas on language and their connections to the theoretical and philosophical considerations of his predecessors reveals his relativistic and deterministic conception of language. According to this conception, language is a central influencing factor in perception and cognition, constitutively bound to its use in thought collectives.

Tarnschrift - Markewitz, Friedrich; Bäumer, Benjamin (Diskursmonitor. Glossar zur strategischen Kommunikation in öffentlichen Diskursen)

Diskreditieren - Markewitz, Friedrich (Diskursmonitor. Glossar zur strategischen Kommunikation in öffentlichen Diskursen)

Rezension Brommer, Sarah/Roth, Kersten Sven/Spitzmüller, Jürgen (Hg.) (2022): Brückenschläge. Linguistik an den Schnittstellen - Markewitz, Friedrich (Journal für Medienlinguistik)

Rezension Takada, Hiroyuki. 2024. Hitlers Reden 1919–1945. Eine sprachwissenschaftliche Analyse - Markewitz, Friedrich (Zeitschrift für Angewandte Linguistik)

Fachsprache - Markewitz, Friedrich (Wörterbücher zur Sprach- und Kommunikationswissenschaft)

Aphorismus - Markewitz, Friedrich (Wörterbücher zur Sprach- und Kommunikationswissenschaft)

Fachwort - Markewitz, Friedrich (Wörterbücher zur Sprach- und Kommunikationswissenschaft)

Gerontolekt - Markewitz, Friedrich (Wörterbücher zur Sprach- und Kommunikationswissenschaft)

Zensur - Markewitz, Friedrich (Diskursmonitor. Glossar zur strategischen Kommunikation in öffentlichen Diskursen)

The Economics of Ideologies - Gries, Thomas; Burs, Carina; Müller, Veronika
Many of the major international and intrastate crises and conflicts, but also the threat to democratic principles, are driven by belief systems and ideologies. They fuel political polarization, which is particularly evident in the battleground of social media. Nevertheless, we hardly pay attention to ideologies, their narratives, functions and organizations in economic theory today. Ideologies as “non-rational beliefs” seem incompatible with rationality in economic models. Therefore, the book examines the role of ideologies and belief systems in individual decision-making behavior from an economic and rational perspective. Due to the fact that people have incomplete information, belief systems and ideologies fulfill a number of important functions. While ideologies themselves serve psychological needs, they are used as a cognitive framework for rational decision-making once they have been adopted through a Bayesian learning process. They influence decisions in a wide range of areas, from consumption and work to politics. This is where the role of ideological organizations becomes important, because they determine the ideological direction of the narratives and their dissemination. Thus, ideologies give a normative direction, for better or for worse. The “quality” of ideological leadership can be evaluated normatively on the basis of principles such as individual sovereignty and human dignity. A democratic discourse requires an information and communication system that enables an evaluation of precisely these ideologies, free from resource and information power.

Decision-Driven Analytics in Smart Factories: Enterprise Architecture Framework for Use Case Specification and Engineering (FUSE) - Weller, Julian; Dumitrescu, Roman (Electronics)
This paper presents a comprehensive design framework for Enterprise Architecture aimed at facilitating decision-driven analytics in smart factories. The motivation behind this research lies in challenges faced by manufacturing companies, such as skilled labor shortages and increasing global competition, alongside the imperative for sustainable production. This journal provides a novel approach for designing and documenting prescriptive analytics use cases in manufacturing environments. The framework addresses the need for effective integration of advanced data analytics and prescriptive analytics solutions within existing production environments, thereby enhancing operational efficiency and decision-making processes. A Design Science Research approach is used to iteratively derive a framework based on stakeholder needs and activities along the prescriptive analytics use case development cycle. The resulting framework is demonstrated and evaluated in an IoT Factory setup in a research facility. From a practical perspective, the framework supports manufacturing companies in systematically designing prescriptive analytics use cases. From a research perspective, it contributes to the body of knowledge on Enterprise Architecture Management (EAM) by operationalizing the design of prescriptive analytics use cases in manufacturing contexts. The main contributions of this study include the development of a framework that supports the planning, design, and integration of prescriptive analytics use cases. This framework fosters interdisciplinary collaboration and aids in managing the complexity of data-driven projects.

Mache dich auf, werde licht! Ein Abriss des weihnachtlichen Ab und Auf anhand des Weihnachtsfilms von Penny 2022 Der Riss / Let's Talk - Schroeter-Wittke, Harald (Weihnachts-Werbespots als moderne Krippenspiele)

Quelleninventare als Forschungsmittel. Zum Potenzial der Netzwerkanalyse in der Repertoireforschung - Plaksin, Anna Viktoria Katrin; Stremel, Sophie (Die Tonkunst)

Trendbericht: Organische Chemie 2025 - Breugst, Martin; Andexer, Jennifer; Barra, Lena; Beil, Sebastian B.; Bierbach, Sascha; Burkhardt, Immo; Dumele, Oliver; Ernst, Martin; Frommer, Jennifer; Gellrich, Urs; Germer, Philipp; Giese, Michael; et al. (Nachrichten aus der Chemie)
Abstract Highlights von November 2023 bis 2024: die erste Einelektron‐C–C‐σ‐Bindung und Anti‐Bredt‐Verbindung; gesättigte Heterocyclen elektrochemisch funktionalisieren; Ausrichten diskotischer Flüssigkristalle; enantioselektive Wagner‐Meerwein‐Umlagerung reiner Aliphaten; photokatalytisch von Furanen zu Pyrrolen; mit Ammoniak zu primären Arylaminen; Metallschrott recyceln mit ionischen Flüssigkeiten; terminale Alkene mit Ni‐Katalysatoren zum (Z)‐ oder (E)‐Alken isomerisieren;neue Fungizide, Medikamente und Alkaloide.